الاتجاه الاجتماعي في التفسير عند قريش شهاب وموقفه من قوامة الرجال : دراسة تحليلية - عمر، عبد الرحمن فهد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The social trend in the interpretation of the Quran is so significant that it has gained momentum today, therefore, has been regarded as a new method of interpreting the Quran based on social reality. This breakthrough has changed the way scholars deal with a Quranic text. Likewise, it has proven its validity in bringing about social change with no narrow-mindedness or bigotry to the views and statements of later and former scholars. This new method of social interpretation of the Quran has enable scholars to deduce benefits and exclusive conclusions from the Quranic text as a solution to material as well as spiritual uncertainties of societies. From this standpoint, contemporary scholars aim to find answers to concerns and problems faced by societies. They aim to respond to the suspicions and misgivings raised about the Quran and Shariah. An example of this social interpretation is 'tafsir al-Misbah' by Quraysh Shihab. The researcher uses two approaches: inductive and analytical. He uses the inductive approach to read through books of Islamic exegesis and the writings of Quraysh Shihab on social trend in the interpretation of the Quran meant to deal with contemporary issues. He also uses the analytical approach in explaining the concept of Qiwamah (man's guardianship in a household of a woman) and the impact of social trend in the interpretation of the Quran on understanding the nature of that Qiwamah and all the misgivings that surround it. The research has concluded that: the significance of the social trend in interpretation of the Quran lies in its unique quality in bringing the Quran down to popular understanding as well as in presenting a key solution to recurrent contemporary problems. That Muhammad Quraysh Shihab has drawn on the writings of the proponents of the social trend in interpretation of the Quran in order to reconcile 'text' and 'reality'. That there is no evidence whatsoever for the claim made by the opponents of the Quran that Islam has infringed the rights of women and has stripped her of freedom. Qiwamah is an honor for women—it is rather authority of guardianship not that of subjugation, control or violence. Finally, contemporary social realities and issues have proven, by the testimony of writers and intellectuals including non-Muslims, that whatever brought by Shariah Law is valid—all these have equally shown that the social trend in interpretation of the Quran is valid and that it plays a key role in solving and overcoming social problems.